(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Despite the presence of numerous publications and analytical reviews in the international literature, a universally accepted algorithm for the surgical treatment of Chiari malformation type I (CM-I) does not currently exist. In the domestic literature, the number of publications devoted to the surgical management of CM-I remains limited, which, in our opinion, highlights the relevance of this study.